Implementasi Asas Fair Trial dan Open Justice dalam Legal Memorandum dan Eksaminasi sebagai Sarana Pengawasan Akuntabilitas Hakim - Andika Kelvin Franata Pakpahan; Bambang Fitrianto; Nico Saputra Nasution; Ahmad Ridwan Nasution (Pusat Riset dan Inovasi Nasional, 2025)
The enforcement of fair and transparent justice requires a firm guarantee of the principles of fair trial and open justice within the judicial system. These two principles are fundamental to the protection of human rights and serve as essential mechanisms to ensure the accountability of judges as executors of judicial power. This study aims to analyze the implementation of fair trial and open justice principles in judicial oversight practices through the instruments of legal memorandum and public examination (eksaminasi). This research employs a normative method with a statutory and document-based approach. The findings indicate that although not formally regulated as part of Indonesia’s judicial oversight system, legal memoranda and examinations play a significant role in enabling public participation and control over judicial independence and integrity. Strengthening these instruments can serve as an effective strategy to realize an accountable, transparent judiciary that upholds procedural justice.